Does COVID-19 pandemic moderate financial leverage, firm size, and dividend pay-out ratio on systematic risk (beta) of stock? - Mahendra, I Kadek Rian; Suaryana, I Gst. Ngr. A. (International research journal of management, IT and social sciences, 2023)
The purpose of this study was to obtain empirical evidence regarding the effect of financial leverage, firm size, and dividend payout ratio on the systematic risk (beta) of stocks with the Covid-19 pandemic as a moderating variable. The data used is secondary data obtained from annual reports of LQ-45 index companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The data analysis technique used was the sub-group moderation. The total population in this study was 45 companies listed in the LQ-45 index, using the purposive sampling method, where 115 observations were obtained. The research results show that: 1) financial leverage has a positive effect on the systematic risk (beta) of stocks; 2) firm size has no effect on the systematic risk (beta) of stocks; 3) dividend payout has a negative effect on the systematic risk (beta) of stocks; 4) the COVID-19 pandemic strengthened the effect of financial leverage on the systematic risk (beta) of stocks; 5) the COVID-19 pandemic was unable to moderate the effect of firm size on the systematic risk (beta) of stocks; and 6) the COVID-19 pandemic strengthened the effect of the dividend payout ratio on the systematic risk (beta) of stocks.